2018
DOI: 10.24820/ark.5550190.p010.466
|View full text |Cite
|
Sign up to set email alerts
|

Indole anion cycloadditions with methyl coumalate

Abstract: DedicationWe honor Professor Gordon Gribble on his distinguished career in organic chemistry. His legacy of versatile synthetic methodology and total synthesis will continue to be valued by both academic and industrial researchersReceived 01-02-2018 Accepted 01-27-2018 Published on line 02-27-2018 AbstractThe reaction of the anion of indoles with methyl coumalate followed by selective opening of the lactone led to the preparation of tricyclic intermediates for indole alkaloid synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…[21] Recently,K raus andc o-worker found that indolemagnesium iodides, generated in situ from nonprotectedi ndoles 72 with methylmagnesium iodide, reacted with methyl coumalate 12 a to access dihydrocarbazoles 73 in an inverse-electron-demand fashion (Scheme 17). [22] When 3-alkylindoles 72 b and 72 c were used as dienophiles, bridged lactones 74 could be isolated and characterized, but both of them underwent retro-DA reactions at room temperaturet og ive the starting materials. Under further treatmentw ith trifluoromethanesulfonic acid, bridged lac-tones 74 were convertedi nto dihydrocarbazoles 73 through lactone-opening reactions.…”
Section: Iedda Reactions Of 5-carbonyl-2-pyronesmentioning
confidence: 99%
“…[21] Recently,K raus andc o-worker found that indolemagnesium iodides, generated in situ from nonprotectedi ndoles 72 with methylmagnesium iodide, reacted with methyl coumalate 12 a to access dihydrocarbazoles 73 in an inverse-electron-demand fashion (Scheme 17). [22] When 3-alkylindoles 72 b and 72 c were used as dienophiles, bridged lactones 74 could be isolated and characterized, but both of them underwent retro-DA reactions at room temperaturet og ive the starting materials. Under further treatmentw ith trifluoromethanesulfonic acid, bridged lac-tones 74 were convertedi nto dihydrocarbazoles 73 through lactone-opening reactions.…”
Section: Iedda Reactions Of 5-carbonyl-2-pyronesmentioning
confidence: 99%